Citizenship and Social Policy: the Debate on the Citizen’s Income - Jean-Paul Révauger (Revue Française de Civilisation Britannique)
The citizenship income, or « basic income » is an old idea, dating back to the 1920’s. Launched by progressive utopians, it was taken up in the 1930’s by the Social Credit movement, which hovered between quackery and social experimentation. It was peddled as an alternative to the Beveridgian Welfare State by ultra-liberals, from the 1940’s onward, but is also popular among ecologists and anarchists who welcome the end of waged work and of the definition of social identity through work. Today, as an elegant companion for austerity and for the crisis, is it in tune with conservative policies.